Evaluasi Program Musyawarah Guru Mata Pelajaran Fikih Madrasah Tsanawiyah di Kabupaten Karawang - Abdul Haq; Musringudin Musringudin (Universitas Indraprasta PGRI Jakarta, 2022)
This study aims to evaluate the Fiqh MGMP program in Karawang, especially those related to Human Resources, infrastructure, and funding. This research is an evaluation research using the CIPP model approach, that is Context, Input, Process, and Product. Respondents in this evaluation were administrators and members of the MGMP Fiqh MTs in Karawang. This evaluation research was carried out in 2022 with the sampling method carried out was purposive sampling. The data were collected using interviews, observation and documentation. The three types of data were tested for validity using triangulation techniques. The evaluation results showed that the planning aspects of the MGMP program are generally good. Aspects of human resource capacity, infrastructure, and funding sources that support the MGMP program are still not optimal. The process aspect still does not fulfill all the components specified in the process evaluation aspect. The implementation of MGMP program activities is still very low. Aspects of the achievement of the MGMP program in improving the professionalism of Fiqh subject teachers are still quite good in accordance with the success criteria set in the product evaluation aspect.